A Key Management Method Based on Dynamic Clustering for Sensor Networks. (8th July 2015) - Zhang, Ying; Zheng, Bingxin; Ji, Pengfei; Cao, Jinde
Abstract : Many cluster-based routing protocols had been proposed which had rarely considered the network security issues so far. The existing key management methods have imperfection when they combine with cluster-based routing protocols. Normally cluster-based key management method has better performance than the distributed key management method, but most of the layer-cluster key management methods do not consider the problem of key updating and being captured for cluster heads. Considering the nodes' capture probability, particle swarm optimization algorithm was used to optimize the clustering of sensor networks. A dynamic key management method was proposed to achieve key updating regularly and provided a security strategy for sensor networks to solve the problem of being captured for cluster heads. The simulation illustrates that the proposed key management method can achieve better security performance.